2014
DOI: 10.1159/000366175
|View full text |Cite
|
Sign up to set email alerts
|

Personal Genomics in Greece: An Overview of Available Direct-to-Consumer Genomic Services and the Relevant Legal Framework

Abstract: Background: This article provides an overview of direct-to-consumer (DTC) genomic services that are currently available in Greece and the legal framework within which they operate. Methods: Here, we describe the landscape of the DTC genomic testing companies and laboratories by conducting a systematic Ιnternet search for relevant websites. We examine the existing legal framework regarding genetic testing in Greece by a review of present regulation. Although Greece does not have explicit legal provisions for DT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Both studies emphasized a lack of exhaustive information on the privacy policy regarding minors, which is a deviation from the professional guidelines on this issue. Also, in a recent systematic Internet search for DTC genomic services, limited information on privacy policies was found [ 120 ]. This evidence contrasts with other studies that found the majority of sites selected provided this information [ 115 - 117 , 121 , 122 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies emphasized a lack of exhaustive information on the privacy policy regarding minors, which is a deviation from the professional guidelines on this issue. Also, in a recent systematic Internet search for DTC genomic services, limited information on privacy policies was found [ 120 ]. This evidence contrasts with other studies that found the majority of sites selected provided this information [ 115 - 117 , 121 , 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…Very little information or scientific evidence was provided on the clinical validity of tests [ 114 - 117 , 121 - 123 , 128 ]. Some websites referred to a laboratory certification, such as Clinical Laboratory Improvement Amendments (CLIA) standards, to indicate legitimacy [ 114 , 115 , 117 , 120 - 122 , 124 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although stringent standards apply to genetic testing conducted in Australia, the TGA and other regulators are not empowered to prevent access to or regulate the quality of Internet-based DTC genetic tests conducted overseas. Similar issues are faced by other international regulators ( 9 ), with issues reported such as difficulties determining whether DTC samples were being processed locally or sent overseas ( 11 ). Given the challenges of genomic literacy in the general population ( 19 , 20 ), many consumers may not be aware of the quality of online genetic tests.…”
Section: Concerns With Unaccredited Internet-based Dtc Genetic Testsmentioning
confidence: 89%
“…15 Also, we used structured questionnaires, face-to-face interviews, and surveys to assess the opinion and standpoint of the various stakeholders in Greece, such as the Ministry of Health, National Medicines Organization, payers and insurance companies, and others. 16 Lastly, we have documented the existing genetic laboratories in Greece 17,18 and currently, this information is being compiled into a data repository to be directly assessible from the general public and clinicians. Through the use of questionnaires and structured surveys, we have assessed the level of genomics awareness and genetic education of the general public and of healthcare professionals, respectively, [19][20][21] and evaluated the academic educational environment in Greece as far as pharmacogenomics is concerned, both at the under-and post-graduate levels 22 and we have developed elearning courses in the field of genomic medicine ensuring continuous medical education of interested healthcare professionals and biomedical scientists.…”
Section: Key Componentsmentioning
confidence: 99%